Pengaruh Fasilitasi Neuromuskular Proprioseptif terhadap Fleksibilitas dan Kelincahan pada Atlet Sepak Bola - jan jan bintang; Asep Angga Permadi; Irwan Hermawan (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. Improving physical performance is crucial for football players, where flexibility and agility are key components that affect movement efficiency and injury prevention. This study aims to determine the effect of Proprioceptive Neuromuscular Facilitation (PNF) training on improving the flexibility and agility of football players. Materials and Methods. Total of 25 football players from Persigar Garut participated in a one-group pre-test and post-test experiment. Flexibility was measured using the Sit and Reach Test and agility was measured using the Illinois Agility Sprint Test. The validity and reliability of the instruments were ensured to guarantee the accuracy of the measurements. Results. Data analysis using the paired t-test showed a significant improvement ($p < 0.05$) in both factors after the intervention. Average flexibility increased by 23.8% and agility increased by 12.26%. These results confirm that PNF training effectively improves both performance variables. Conclusion. PNF exercises are recommended as an effective method for improving athletes' range of motion and speed of change of direction. The contribution of this study is to provide a scientific basis for incorporating PNF as a standard training programme, and further research can focus on comparing PNF with other stretching methods and its impact on long-term injury prevention